An Optimistic Approach for Load Balancing in Cloud Computing - Sharma, Meenakshi; Anitha Y; Sharma, Pankaj (International Journal of Computer Sciences and Engineering, 2014)
Cloud computing technology is changing the focus of IT world and it is becoming popular because of its great characteristics. Load balancing is one of the main challenges in cloud computing. Load balancing is the methodology to distribute the load across multiple servers or a cluster of servers, databases or other resources. Efficient load balancing helps to optimize the server usage, increase throughput, and decrease response time. The objective of this paper to propose a load balancing algorithm that can provide an efficient load balancing. The results discussed in this paper are based on existing round robin, least connection, throttled, fastest response time and the new proposed algorithm. This new algorithm improves the overall response time and data centre processing time as well as reduce the cost, in comparison to the existing algorithms.